Wildfire impacts on schools and hospitals following the 2018 California Camp Fire - Schulze, Stefanie S.; Fischer, Erica C.; Hamideh, Sara; Mahmoud, Hussam (Natural hazards (Dordrecht), 2020)
Wildfire impacts on communities have become more pronounced in recent years as the intensity and frequency of wildfires have increased in densely populated areas of the USA. Communities located in the wildland–urban interface (WUI) neighboring high wildfire risk zones are at highest risk of damage to civil infrastructure. This paper summarizes an investigation on the 2018 Camp Fire impacts to schools and healthcare facilities in Paradise, CA. The paper demonstrates that interdisciplinary data collection methods can provide a comprehensive overview of school and hospital damage after a wildfire. Photographs, light detection and ranging (LiDAR) scans of damaged buildings, drone aerial images, and interviews with key school and healthcare stakeholders provided valuable information on the structural and nonstructural damages to infrastructure. Interviews also provided context to the impacts of infrastructure damage on the ability of education and healthcare facilities to operate or reopen following the fire. Nonstructural damage to schools and hospitals, such as damage to electrical systems or other utilities, significantly impacted the functionality of these facilities. Understanding the vulnerabilities of WUI communities to wildfire will help with disaster mitigation and recovery planning and aid in restoring critical services after the disaster.